EFFECT OF SELENIUM, SULPHUR AND THEIR INTERACTION ON YIELD OF ONION (Allium cepa. L) AND SUNFLOWER (Helianthus annus. L) - S.A. HUSSAIN, A. JESSIE REBECCA, P. SURENDRA BABU, M. CHANDINI PATNAIK and (The Journal of Research, PJTSAU, 2019)
Selenium (Se) is an important trace element in animal and human nutrition but known as a nonessential element for plants, though its beneficial roles have been reported in the plants capable of accumulating large amount of the element (White et al. 2007). It plays an important role in body antioxidation system; it is considered as an individual antioxidant that can cooperate with other antioxidants such as vitamins C and E in the processes protecting the cells from free radicals.